Effect of screening for type 1 diabetes on early metabolic control: the DiPiS study - Lundgren, Markus; Jonsdottir, Berglind; Elding Larsson, Helena (Diabetologia, 2019)
Aims/hypothesis It has been shown that children previously enrolled in follow-up studies have better glycaemic control during the early period after diabetes diagnosis. The aim of this study was to analyse glycaemic control over a longer period, past the period of partial remission, after diagnosis in children followed before diagnosis in the Swedish Diabetes Prediction in Skåne (DiPiS) study compared with children of equal age not enrolled in pre-diabetes follow-up, receiving equivalent diabetes care. Methods HbA 1c from diagnosis and for the following 5 years, as well as differences in insulin dosage, BMI, pump use, partial remission according to insulin dose-adjusted HbA 1c and baseline demographics were compared between children who were enrolled in follow-up and had received information on diabetes risk ( n = 51) and children not enrolled in follow-up ( n = 78). Results The group followed before diagnosis had a higher proportion of first-degree relatives (FDRs) with diabetes (28% vs 5.6%; p = 0.001) and a higher proportion of participants with mothers born in Sweden (100% vs 89%; p = 0.02). No significant differences in total daily insulin dose, pump use or other baseline sociodemographic factors were detected between the groups. Median HbA 1c at diagnosis and at 1, 2, 3, 4 and 5 years after diabetes diagnosis was significantly lower in children followed before diagnosis (all p < 0.05), and was not related to FDR status. Conclusions/interpretation Compared with controls not previously enrolled in follow-up, our study shows that children enrolled in longitudinal follow-up before the diagnosis of diabetes have better glycaemic control, measured by HbA 1c , up to 5 years after diagnosis and during the initial period of partial remission. Improved glycaemic control in the initial years of living with type 1 diabetes could affect long-term outcome and complications and might also improve study enrolment in future longitudinal studies.